14 Leg pains in congenital heart disease. (2nd February 2018) - Coats, L; Best, K; Chaudhry, B; Crossland, D; Hutchinson, S
Abstract : Purpose: To assess the burden and nature of leg pains in children and young adults with congenital heart disease. Methods: Leg pains were identified as an issue of concern to patients by Little Hearts Matter. A survey was designed and distributed by e-mail. Responses were pseudo-anonymised and descriptive statistics performed. Results: 220 patients responded [57% male, 8.3 years (0–29), 66% single ventricles]. 92% patients reported leg pains with 44% occurring on a daily basis. In the patients' siblings (n=107), leg pains were less frequent (30%, p<0.001). In patients, pain was typically in the lower legs or around the knees or ankles, often associated with crying and screaming and most commonly occurred at night-time (76%). Analgesia (60%) or massage (50%) was the preferred option for alleviation. Frequency of pains did not differ between those with biventricular circulations and single ventricles (p=0.49). There was no gender bias and history of a shunt or Fontan circulation did not confer risk. Stress was a more common precipitant in older patients (p=0.02) who also tended to experience nocturnal pain more often. Interestingly, patients with atopy (asthma/eczema, n=22) reported a higher frequency of leg pains, which was borderline significant (p=0.06) with dehydration a reported stimulant in this group. Patients on warfarin tended to experience fewer leg pains (p=0.07). Conclusion: Leg pains are more frequent in those with congenital heart disease than their healthy siblings. Aetiology is uncertain but pains share common characteristics with benign 'growing pains'. Further investigation into the causes of this distressing symptom is warranted.